PENGARUH FENOMENA METI KEI TERHADAP PERILAKU SOSIAL DAN KEPEDULIAN LINGKUNGAN PADA SISWA SEKOLAH MENENGAH DI MALUKU TENGGARA - Mustova Namsa; Sukadari (Program Magister Pendidikan IPS UPY, 2025)
This study aims to provide an understanding of the importance and meaning of a tradition that continues year after year, particularly in transmitting its values to younger generations—especially adolescents or secondary school students in Southeast Maluku Regency—who are perceived to have been significantly influenced by external cultures affecting their social life. It explores the impact of the studied tradition, namely the Meti Kei phenomenon, and its effects on the surrounding environment as well as on the social behavior of secondary school students in the region. This research adopts a qualitative research design, with the objective of offering an in-depth description of the phenomena experienced by the research subjects—such as their behaviors, perceptions, experiences, or motivations—in their natural context. The findings of this study are expected to be utilized optimally for the benefit of future generations, serving as a reference for further research and contributing to shared knowledge and benefits.